2003
DOI: 10.1093/jnci/95.12.868
|View full text |Cite
|
Sign up to set email alerts
|

Lead Times and Overdetection Due to Prostate-Specific Antigen Screening: Estimates From the European Randomized Study of Screening for Prostate Cancer

Abstract: These model-based lead-time estimates support a prostate cancer screening interval of more than 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
610
0
23

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 943 publications
(659 citation statements)
references
References 36 publications
18
610
0
23
Order By: Relevance
“…5 Recently, attention has been directed toward creating algorithms or nomograms that combine multiple clinical and laboratory features into risk scores to help in clinical decision making. [5][6][7][8] Nomograms are risk assessment tools that combine multiple clinical and laboratory risk factors to inform clinical decision making about biopsy, risk classification, and/or treatment options. Although there is wide variation in the manner in which the algorithms and nomograms have been developed and validated, a recent systematic review suggested that these tools tend to provide more accurate diagnostic predictions for cancer-positive biopsies than the use of PSA testing or other factors alone.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, attention has been directed toward creating algorithms or nomograms that combine multiple clinical and laboratory features into risk scores to help in clinical decision making. [5][6][7][8] Nomograms are risk assessment tools that combine multiple clinical and laboratory risk factors to inform clinical decision making about biopsy, risk classification, and/or treatment options. Although there is wide variation in the manner in which the algorithms and nomograms have been developed and validated, a recent systematic review suggested that these tools tend to provide more accurate diagnostic predictions for cancer-positive biopsies than the use of PSA testing or other factors alone.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%
“…Although there is wide variation in the manner in which the algorithms and nomograms have been developed and validated, a recent systematic review suggested that these tools tend to provide more accurate diagnostic predictions for cancer-positive biopsies than the use of PSA testing or other factors alone. 6 Recent reports described the use of PCA3 testing to identify patients with aggressive versus indolent prostate cancer. [9][10][11][12][13][14][15][16][17][18][19][20][21] Results of studies have been mixed.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%
“…Within the screening arm of the ERSPC (section Rotterdam, the Netherlands), 27-56% of all cancers detected in men aged 55-75 years can be classified as potentially overdiagnosed. 18 …”
Section: Incidence and Mortality Of Pcmentioning
confidence: 99%
“…It is estimated that a PSA screening programme will detect prostate cancers an average of 10-14 y prior to when they would have been diagnosed clinically (lead time bias). 4 Furthermore, given that prostate cancer often progresses only slowly, and that men are typically diagnosed in late middle age, early detection using PSA testing risks overdiagnosis, that is death from other causes before the cancer would have become symptomatic. The proportion of cases identified by PSA screening that are overdiagnosed is uncertain, and estimates vary between 29% 5 and 84%.…”
Section: The Natural History Of Early Prostate Cancermentioning
confidence: 99%